Economic Transformation through Ecopreneurship: Analysing the Potential of Demographic Bonus and Human Resource Management Towards Golden Indonesia 2045 - Silalahi, Rudi Yanto Batara; Hendriati, Yossi (Dinasti Publisher, 2024)
This study aims to determine the role of ecopreneurship in supporting Indonesia's economic transformation towards the Golden Indonesia 2045, with a focus on the potential of demographic bonuses and human resource management in students in Batam City. The research method is descriptive quantitative and qualitative. The results showed that students' interest in ecopreneurship is quite high, but there are barriers in terms of capital availability, technical skills, ecopreneurship literacy, and limited ecopreneurship communities among students. There are 9 strategies that can be applied to support ecopreneurship, with this strategy it is hoped that ecopreneurship can become the main driver of sustainable economic transformation towards Golden Indonesia 2045